2013
DOI: 10.1111/1574-6941.12080
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional variation in soil fungal communities associated with litter bags containing maize leaf

Abstract: Soil fungi are key players in the degradation of recalcitrant organic matter in terrestrial ecosystems. To examine the organisms and genes responsible for complex organic matter degradation in soil, we tracked changes in fungal community composition and expressed genes in soil adjacent to mesh bags containing maize leaves undergoing decomposition. Using high-throughput sequencing approaches, changes in fungal community composition were determined by targeting 18S rRNA gene sequences, whereas community gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 62 publications
7
32
1
Order By: Relevance
“…Our results are consistent with the description of lower abundance of Chytridiomycota by Lienhard et al (2014) under no-till system as compared to conventional tillage, according to the ability of this phylum to have resistant structures that permit survival through periodic drying and high summer temperatures typically occurring under tilled soils (Gleason et al 2004). Similarly, Artz et al (2007) detected no Chytridiomycota sequences in peatlands abandoned for more than 5 years, whereas Kuramae et al (2013) observed Chytridiomycota in buried maize leaves. Therefore, our data support the hypothesis that this phylum contributes to the decomposition of crop residues with a high C:N ratio.…”
Section: Effect Of Land-use Intensification and Soil Properties On Phsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results are consistent with the description of lower abundance of Chytridiomycota by Lienhard et al (2014) under no-till system as compared to conventional tillage, according to the ability of this phylum to have resistant structures that permit survival through periodic drying and high summer temperatures typically occurring under tilled soils (Gleason et al 2004). Similarly, Artz et al (2007) detected no Chytridiomycota sequences in peatlands abandoned for more than 5 years, whereas Kuramae et al (2013) observed Chytridiomycota in buried maize leaves. Therefore, our data support the hypothesis that this phylum contributes to the decomposition of crop residues with a high C:N ratio.…”
Section: Effect Of Land-use Intensification and Soil Properties On Phsupporting
confidence: 91%
“…For this reason, the SSU rRNA region is considered more suitable for comparing and for discerning the highest fungal phylogenetic ranks (i.e., phyla and orders), and therefore, it is useful for an initial assessment of the total soil fungal community (Hunt et al 2004) also when using the most recent high-throughput sequencing techniques (Kuramae et al 2013;Lienhard et al 2014). Moreover, the SSU rRNA region is known to be a successful marker for Chytridiomycota identification (Freeman et al 2009), and it generally has a higher discriminatory power for basal fungi (including Zygomycota) compared to both the ITS region and the nuclear ribosomal large subunit (LSU; Schoch et al 2012).…”
Section: Sampling and Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for this discrepancy may be related to the range of soil P (1.8–17 mg·kg −1 in Lauber10 and 1.65–3.31 mg·kg −1 in our study). Zygomycota , as saprotrophic species, are responsible for decomposing plant litter, alter soil chemical properties4350. This was mirrored by most of the differences between the dystrophic bare land site and the other forest sites.…”
Section: Discussionmentioning
confidence: 99%